A timings analysis of the return of serve in wheelchair tennis to infer the importance of anticipation of serves - Deshpande, Y.; Jackson, R.; King, M.; Cockram, A.; Goosey-Tolfrey, V. (BASES Conference 2024, 2024)
The prevalence of anticipatory behaviour in any interceptive action depends on the spatio-temporal demands of the task. With no existing research exploring the time constraints in wheelchair tennis (WT), the role of anticipation in effectively returning WT serves is unknown. Therefore, the aims of this study were (1) to quantify the time constraints in the serve return dyad in WT, (2) to understand the relationship between serve quality, receiver response, and return shot outcomes, and (3) discuss the importance of anticipation skill in WT serve returns. Video footage of 369 returns-of-serve by 19 profes sional wheelchair tennis players (10 from men`s open, 5 from women`s open, 4 from quad`s) in 13 matches from international tournaments were analysed to calculate ball transit time (TT), serve accuracy, the returner`s movement initiation time (MIT), movement time (MT) and the quality of the returner`s position just before ball contact. Repeated measures correlations were calculated between the timing variables. One linear multi-level model was used to compare timing variables between first and second serves and another was used to determine the relationship between the timing variables and the shot out come variables. Significant difference in TT was observed between first and second serves. However, no significant dif ference in average MIT (M = ~300 ms) was observed (Cohen`s d = .44, P = .65). Thus, returners initiated lateral movement at the same time irrespective of different serve speeds. This sug gests that pre-contact kinematic information from the server`s action and ball toss might be used to calibrate their return movement and determine when to initiate their response. MIT was a non-significant predictor of return outcomes (Cohen`s d = .75, P = .30), i.e., earlier or later initiation of lateral movement towards the ball was not related to more offensive or defensive return outcomes, respectively. Lower TT (P = .01, Cohen`s d = 2.67) and more accurate serves (P < .001, Cohen`s d = 5.09) predicted a more defensive pre-contact returner position. Also, for first serves, players were in a defensive pre contact position on 29.4% of returns. This suggests there is significant scope for improvement when returning faster first serves in WT. With faster and more accurate WT serves leading to more defensive return outcomes, and serve speeds in WT increasing over the years, players might need to become more attuned to advance information. This would allow them to move earlier and potentially make a higher proportion of offensive return shots.